Inverse dynamic modelling of swimmers impulse during a grab start - Houel, N.; Taiar, R.; Marchand, F. H.; Rey, J. L.; Boissiere, E.; Lecat, S.; Quievre, J.; Hellard, P. (Biomechanics and Medicine in Swimming X, 2006)
Under race conditions, the Start directly influences an athlete's performance. Taking into account the difficulties coming from the specific parameters relative to the start, comparing the swimmer's movement with the kinematic data stays the best approach to understand the motion. The model of the present work was developed through this approach allowing us to pre-dict the swimmer's performance (trajectory, velocity) and the joint moment of each articulation during the impulse phase of the grab Start. This model defines kinematical and dynamical data with the following mean dispersions: 9 % for horizontal and total speed at the instant of take off, l % for the swimmer's internal joint power. By means of this model, it becomes possible to analyze and understand the joint moment of each articulation and the segmental coordination for each swimmer performing a grab start.